PERSPEKTIF GENDER DALAM REPRESENTASI IKLAN - Agung Suwasana, Arief (Institute of Research and Community Outreach - Petra Christian University, 2001)
Reconstructing women to obtain a role equal to that of man requires cognizance on how to reconstruct the dominant ideology of patriarch. Ads representation plays as a means of legitimating or preserving ideology and social phenomena. However%2C ultimately%2C the ads representation also reflects social culture. Abstract in Bahasa Indonesia : Kesadaran untuk merekonstruksi perempuan memperoleh peran yang setara dengan laki-laki memang memerlukan penyadaran bagaimana merekonstruksi dominasi ideologi patriarki. Representasi iklan memang dapat menjadi sarana legitimasi atau pelestari ideologi dan fenomena sosial. Akan tetapi pada akhimya representasi iklan juga menjadi cerminan budaya masyarakat. ideology%2C images%2C culture.